RANCANG BANGUN SISTEM PENGINJEKSIAN LARUTAN IODINE CLOCK BERBASIS INTERNET OF THINGS - Mohammad Ilhammudin Toiyib; Adharul Muttaqin; Panca Mudjirahardjo (Jurnal Mahasiswa TEUB, 2022)
The iodine clock reaction is a chemical reaction that consists of two different colorless solutions mixed into one container to produce a colorless solution and a few moments later the solution turns dark blue. This color change is used as a timer for the stopping mechanism for the chemical-powered car prototype in the Chem E Car team of Universitas Brawijaya. The injection syringe used to inject the iodine clock solution can affect the reaction time of the iodine clock solution due to the difference in pressure at the time of injection so the mixing speed varies. The injection system of iodine clock solution aims to reduce the error of the reaction time of the solution so that it becomes more constant. The system is also equipped with the Internet of Things (IoT) concept which aims to monitor the state of the iodine clock solution such as the temperature of the solution because the competition time is quite long, about 10 hours so that the iodine clock solution must be monitored while not in use. This study uses the YF-S401 sensor as an indicator of the volume of the iodine clock solution. In addition, the system uses an actuator, namely a solenoid valve as a valve for the ex